Microstructure and fracture morphology of thermally sprayed refractory metals and ceramics - Kovarik, O.; Siegl, J. (Проблемы прочности, 2008)
The microstructural characteristics such as porosity, splat morphology and grain size of thermally sprayed coatings made of both ceramic and refractory metals are investigated. Al2O3 and Cr2O3 coatings represent ceramic materials while pure W and Mo coatings represent the refractory metals. The used deposition technology (RF-plasma, gas stabilized or water stabilized DC plasma) was found to influence the coatings microstructure to a great extent by providing different particle impact velocities and temperatures. At the same time the substrate temperature plays an important role as is shown fo r refractory metal coatings deposited at different substrate temperatures. Generally, all investigated coatings contained intrasplat cracks, intersplat pores and voids, individual splats of different degree of deformation and different degree of intersplat sintering, crystal grains formed inside individual splats or extending through many of them. It is shown that the size and abundance of the above-mentioned microstructural features predetermine the fracture morphology of the coating as well as mechanical properties. Исследованы такие характеристики микроструктуры, как пористость, морфология частиц напыления и размер зерна газотермических покрытий из керамики ( Al2O3 и Cr2O3) и тугоплавких металлов ( W и Мо). Установлено, что технология напыления (высокочастотная плазма, газо- или водостабилизированная плазма постоянного тока) оказывает значительное влияние на микроструктуру покрытий при различных температурах и скоростях соударения частиц. В то же время отмечена важная роль температуры подложки для покрытий из тугоплавких металлов, нанесенных при различных температурах подложки. Все исследованные покрытия, как правило, содержали трещины внутри напыленных частиц, поры и полости между частицами, отдельные частицы с разными степенью деформации и межчастичного спекания, кристаллиты, образовавшиеся внутри отдельных частиц или проходящие через несколько таких частиц. Показано, что величина и распространенность указанных особенностей микроструктуры предопределяют морфологию поверхности излома покрытий, а также их механические свойства.